Housing status, mortgage debt and financial burden as barriers to health among older adults in the U.S. Issue 1 (2nd January 2022) - Mehdipanah, Roshanak; Martin, Jaclyn; Eisenberg, Alexa K.; Schulz, Amy J.; Morgenstern, Lewis B.; Langa, Kenneth M.
ABSTRACT: We examine relations between housing status, mortgage, financial burden, and healthy aging among older U.S. adults. We combine cross-sectional data from 2012 to 2014 Health and Retirement Study cohorts. Using regression models, we examined associations between owners and renters, mortgage and non-mortgage holders, financial strain, and difficulty paying bills, and poor self-rated health (SRH), heart condition (HC) and hospitalization (past two years). We find that compared to owners, renters had greater likelihood of poor SRH and hospitalization. Regardless of tenure, financial strain was associated with greater likelihood of poor SRH, HC and hospitalization, while difficulty paying bills was associated with poor SRH and HC. Mortgage holders had lower likelihood of poor SRH. Accounting for mortgage status, financial strain was associated with greater likelihood of poor SRH, HC and hospitalization, while difficulty paying bills was associated with poor SRH and HC. Associations between tenure or mortgage status and health were not modified by either financial burden factors. We conclude that there need to be more robust and inclusive programs that assist older populations with housing could improve self-rated health, with particular attention to renters, mortgage holders and those experiencing financial burden.